2020
DOI: 10.2147/hiv.s242756
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors Affecting Survival Rates Among Adult TB/HIV Co-Infected Patients in Mizan Tepi University Teaching Hospital, South West Ethiopia</p>

Abstract: Background: Tuberculosis (TB) and human immunodeficiency virus (HIV) co-infection was responsible for approximately 300,000 deaths worldwide in 2017. Despite this burden of death, factors associated with the survival of TB-HIV co-infected patients were not adequately studied; and some of the existing evidences are inconsistent. This study was aimed to identify factors associated with survival rates of TB/HIV co-infected patients. Methods: The current study was a retrospective analysis of data extracted from 36… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
2
13
2
Order By: Relevance
“…But, in the present study, the lognormal AFT model was the best fit for the data. The followup period of this study also revealed that there were 29.5% deaths among HIV/TB co-infected patients, which might be comparable with a study of Sanzana [17] and higher and lower than studies of [18][19][20][21][22][23] and [1,16,[24][25][26], respectively. In this study, female patients presented slightly higher survival time than male patients as indicated in the K-M plot of patients, which might show a comparable result with studies of Sanzana [17] and Kosgei et al [27].…”
Section: Discussionsupporting
confidence: 86%
“…But, in the present study, the lognormal AFT model was the best fit for the data. The followup period of this study also revealed that there were 29.5% deaths among HIV/TB co-infected patients, which might be comparable with a study of Sanzana [17] and higher and lower than studies of [18][19][20][21][22][23] and [1,16,[24][25][26], respectively. In this study, female patients presented slightly higher survival time than male patients as indicated in the K-M plot of patients, which might show a comparable result with studies of Sanzana [17] and Kosgei et al [27].…”
Section: Discussionsupporting
confidence: 86%
“…This suggests that pharmacological interactions and overlapping toxicities of anti-TB and ART treatments, immunological reconstitution inflammatory syndrome, and other opportunistic infections, all of which have been linked to early death among TB/HIV co-infected patients, should be managed appropriately. In addition, our findings showed that the median time until death was found to be 17.6 months, which is longer than the previous study's finding which was 10 months reported from the Mizan-Tepi university teaching hospital 4 . Another multicenter study from southwest Ethiopia reported that the median time of death was 15.6 months, which is comparable to the results found in this study 24 .…”
Section: Discussioncontrasting
confidence: 76%
“…A significant proportion of the deaths, 29 (34.5%), took place within the first five months of starting anti-TB medication. This is more than twice as high as the South African findings 32 , however, it is lower than the results from Mizan-Tepi University teaching hospital 4 . This suggests that pharmacological interactions and overlapping toxicities of anti-TB and ART treatments, immunological reconstitution inflammatory syndrome, and other opportunistic infections, all of which have been linked to early death among TB/HIV co-infected patients, should be managed appropriately.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…3 Moreover, most TB deaths occur during the first three months of TB treatment initiation. 4 Mortality during this period has been associated with low CD4 counts, not being on antiretroviral therapy (ART) 5, 6 and low body mass index (BMI) 4 at the time of TB diagnosis, Some studies in HIV negative patients indicate that even after successful completion of TB treatment, up to 59% of patients get lung impairment, 7 and consequently chronic lung disease. 8 Moreover, some observational studies have reported reduced long term survival in TB survivors in the United State, 9 and Vietnam.…”
Section: Introductionmentioning
confidence: 99%